East-African Social Sciences and Humanities Journals active in 2008-2009 - Schmidt, Nora (My University, 2016)
Research Data of „East-African Social Sciences and Humanities Publishing: A Handmade Bibliometrics Approach“, Proceedings of the 21st International Conference on Science and Technology Indicators, València (Spain), September 14-16, 2016. Abstract of the paper: For Eastern Africa, very little information about the SSH knowledge production can be found from a European perspective. Adequate indicators like information-rich bibliographic databases that cover East-Africa-based journals and book publishers are lacking. This research in progress explores their indexing situation in detail, their development, which is closely connected to political history, their (non-)usage, and affiliations as well as career-stages of their authors. Furthermore, it also pays attention to East-Africa-based SSH researchers who use other publication venues. Any bibliometric analysis in this field needs to rely on manual data collection, otherwise it would be heavily biased. This study lays out the foundation for citation analyses, qualitative research on the publications' content and the self-description of East-African scholars against the background of an academic environment that is often described as “international”.
Keywords: Scholarly communication; Social Sciences and Humanities journals; East-African higher education